126k views
4 votes
Enter the values of h and k so that y = x2 + 6x + 10 is in vertex form.

y = (x + ) {blank} 2 + {blank}

User Meligy
by
5.2k points

2 Answers

3 votes
y = x^2 + 6x + 10
y = (x + 3)^2 - 9 + 10
y = (x + 3)^2 + 1


User Eugene Tulika
by
4.8k points
1 vote

we have


y=x^(2) +6x+10

we know that

the equation in vertex form is equal to


y=(x-h)^(2) +k\\

where


(h,k) is the vertex

Group terms that contain the same variable, and move the constant to the opposite side of the equation


y-10=x^(2) +6x

Complete the square. Remember to balance the equation by adding the same constants to each side.


y-10+9=x^(2) +6x+9


y-1=x^(2) +6x+9

Rewrite as perfect squares


y-1=(x+3)^(2)


y=(x+3)^(2)+1


(h,k)=(-3,1)

therefore

the answer is

the equation in vertex form is equal to


y=(x+3)^(2)+1

User AspOnMyNet
by
5.1k points